"I felt that I deserved it" : an Investigation into HIV-related PTSD, traumatic life events, and the personal experiences of living with HIV : a mixed-method study - Boulind, Melissa Jane (Rhodes University, Faculty of Humanities, Department of Psychology, 2014)
There appears to be a growing body of literature focusing on PTSD and HIV-related PTSD (the diagnosis of HIV being the significant traumatic event) amongst HIV-positive samples, but only a few African studies that attempt to estimate the prevalence of PTSD amongst HIV-positive people, and even fewer that attempt to estimate the prevalence of HIV-related PTSD. The systemic review presented in this study is currently fully inclusive and is the most up-to-date available. Estimates of the prevalence of PTSD and HIV-related PTSD in South Africa range from 0.7 to 54.1% and, 4.2 to 40% respectively. The current cross-sectional study made use of a mixed-method approach to investigate traumatic life events, PTSD and HIV-related PTSD within a primary health-care centre in KwaZulu-Natal. The quantitative sample consisted of 159 adults (18-50 years) who were compliant on ARV medication. Using the CIDI-PTSD module, the adapted CIDI-PTSD module for HIV, and IES-R, findings indicated that 62% had reported some kind of traumatic event in their lifetime, with 29.6% of participants meeting the criteria for lifetime PTSD, and 40.9% meeting the criteria for lifetime HIV-related PTSD. Altogether, 57.9% of individuals met the criteria for some form of PTSD (either regular PTSD or HIV-related PTSD), and 12.6% met the criteria for both PTSD and HIV-related PTSD. Of the different categories of traumatic events, interpersonal violence has the highest rate of PTSD, followed by a diagnosis of and living with HIV, and then disaster. Furthermore, the IES-R was compared for its usefulness as a screening measure for PTSD against both the CIDI, but results suggest that it is an inferior screening measure to the PDS. The qualitative study consisted of six participants who were examined using IPA methodology informed by the Ehlers and Clark (2000) Model of trauma. Their experiences revealed experiences of stigma, a number of negative appraisals, negative emotions and coping behaviours. Some of the latter might serve as compensatory mechanisms to avoid negative judgements. Hypervigilance seems to be a feature of ARV-compliance that might confer added vulnerability to PTSD and other anxiety disorders.
Keywords: Post-traumatic stress disorder -- Psychological aspects -- Research -- South Africa -- Kwazulu; HIV infections -- Psychological aspects -- Research -- South Africa -- Kwazulu; HIV-positive persons -- South Africa -- Kwazulu -- Interviews; Psychic trauma -- Research; Stress (Psychology) -- Research